Two new species of Diderma (Physarales, Didymiaceae) from northern China - Zhao, Hui-Nan; Rao, Gu; Yang, Xin-Ya; Li, Xiao; Yu, Hai-Long; Zhang, Bo; Li, Yu (Phytotaxa, 2022)
Diderma is one of the most abundant species in Myxomycetes. Based on the study of morphology and phylogeny, two new species—Diderma liaoningensis (is characterized by grouped sporocarps, the sporocyst with dehiscence lines, capillitium with large brown swelling, spore encircled by a pale line) and Diderma verrucocapillitia (is characterized by depressed plasmodiocarps, verrucose capillitium, red-brown spores)—collected from Liaoning province and Jilin province were introduced. Detailed descriptions and illustrations are presented as well as comparisons to similar species. Phylogenetic analyses were carried out using Maximum Likelihood and Bayesian inference based on small subunit ribosomal RNA sequences (SSU rRNA) of Diderma and related genera. These analyses confirmed the placement of two new species in the genus Diderma. A key to 19 species of Diderma from China is also provided. Holotype specimens have been housed in the Herbarium of the Mycological Institute of Jilin Agricultural University (HMJAU), Changchun, China.